Design, development and analysis of an IoT-based framework for monitoring aquaculture farms. (8th June 2020) - Shareef, Zeenat; Reddy, S.R.N.
Aquaculture is one of the most popular occupations for the people in the coastal regions of India. Thousands of farmers depend on the yield generated from aquaculture business for their livelihood. Due to various factors, the water in fishery farms gets polluted, which hampers the growth and yield of fish and shrimp. The traditional approaches followed by Indian aquaculture farmers to measure water quality in their farms are slow and inaccurate. This paper highlights the design and development of a wireless sensor network (WSN) for Indian aquaculture farmers for real time assessment and control of the water quality in their farms. Such a system offers flexibility, efficiency, remote monitoring and early warning to the farmers to take preventive measures in time. This paper also presents the power consumption of the sensor node and analysis of the network parameters of the designed sensor network in terms of received signal strength indicator (RSSI) and packet loss (%) for its robust and efficient design and deployment.